Travelling During The COVID-19 Pandemic: Mitigating The Needs and Wants - Audrey Adeline; Widya Natassha Rachim; Ramadhanty Cahyaning Rizky (Journal of Event, Travel and Tour Management, 2022)
The research is to study the domestic tourists’ considerations and perceived risks and how they allay the disharmony that occurs between the desire to travel and to stay at home because of the pandemic situation, to their decision making in traveling to Bali. Data were collected through questionnaires to 96 domestic Bali tourists and interview with 5 individuals from them to gain deeper insights on the travel decision-making process between January-February 2022, a point where the COVID-19 case in Indonesia rose once again after its stagnant low case report in the third quarter of 2021. Regression analysis was performed and suggest that there is an impact between the perceived risk on purchase decision-making. In addition, results revealed that for the most part, these domestic tourists tend to set aside their worries about COVID-19 and other safety concerns so that their choice to visit Bali can be more prominent, essentially because of feeling weary with the pandemic situation which makes them feeling the urgency to escape from the “routine”.